Ovarian Microcystic Stromal Tumor: A Rare Clinical Manifestation of Familial Adenomatous Polyposis. (November 2016) - Liu, Cheng; Gallagher, Renee L.; Price, Gareth R.; Bolton, Elizabeth; Joy, Christopher; Harraway, James; Venter, Deon J.; Armes, Jane E.
Abstract : Microcystic stromal tumor (MST) is a rare tumor of presumed sex-cord stromal differentiation. We present a case of MST arising within a patient with constitutional 5q deletion syndrome, whose deletion encompassed the APC gene. Genomic analysis of the MST revealed a point mutation in the remaining APC allele, predicted to result in abnormal splicing of Exon 7. Subsequent clinical investigation revealed multiple gastrointestinal polyps qualifying for a diagnosis of familial adenomatous polyposis. This case emphasizes the importance of an aberrant Wnt/β-catenin pathway in the development of MST and adds credence to the inclusion of MST as a rare phenotype of familial adenomatous polyposis. In a search for additional genetic aberrations which may contribute to the development of this rare tumor, genomic analysis revealed a frameshift mutation in FANCD2, a protein which plays a key role in DNA repair. This protein is expressed in human ovarian stromal cells and FANCD2 -knockout mice are known to develop sex cord-stromal tumors, factors which further support a possible role of aberrant FANCD2 in the development of MST. Abstract : Supplemental Digital Content is available in the text.